Association of Children's Dietary Inflammatory Index with Depression and Anxiety Symptoms in Adolescents: Mediating Role of Inflammation and Cardiometabolic Risk Factors - Sahin, Kezban; Yardimci, Hulya; Acik, Murat; Akman, Alkim Oden; Yuksel, Fadime (Imr Press, 2025)
Background: Evidence is scarce on the mechanisms involved in the relationship between dietary inflammatory index and mental health in adolescents. This study aimed to assess the association between children-DII (C-DII) and depressive and anxiety disorder symptoms in adolescents and to explore whether inflammation and cardiometabolic risk factors mediate this association.Methods: The study was conducted at the Ankara City Hospital Pediatrics Polyclinic and 304 adolescents. In cross-sectional study, adolescents were asked general information questions. Anthropometric measurements were performed and some biochemical parameters and inflammation (C-reactive protein (CRP)) were obtained. The C-DII score was calculated from 24-h dietary recalls. Depression and anxiety levels of the participants were assessed by self-report. Structural equation modelling analyzed how cardiometabolic risk factors and inflammation mediate the relationship between mental health and dietary inflammation.Results: C-DII scores were positively associated with depression and anxiety score (beta [95% confidence interval (CI)] = 0.224 [0.08-0.25] for depression; 0.923 [0.04-1.67] for anxiety). Except for dietary inflammation with anxiety in girls, these relationships remained statistically significant in all subgroups by sex. It was determined that CRP partially mediated the relationship between dietary inflammation and depression and anxiety. It was determined that body mass index (BMI)-z score and waist circumference (WC) mediated the relationship between dietary inflammation and depression scores.Conclusions: Our findings indicate that the higher pro-inflammatory potential of diet is associated with a higher risk of depression and anxiety, and this association may be mediated by CRP for depression and anxiety, WC, and BMI-z score for only depression. Further research is required to verify our findings and clarify the latent mechanism in larger populations.
Keywords: C-DII; depression; anxiety; inflammation; adolescents